TINJAUAN ATAS PROSEDUR PENGGAJIAN MENGGUNAKAN ZAHIR 5.1 PADA PT. DATA ENERGY INFOMEDIA - Rizal Firmanto, - (2018)
In carrying out business activities each company has several procedures that are bound by government regulations, one of which is the procedure for paying employee salaries. This procedure is applied to improve the efficiency of salary payments appropriately and minimize errors and irregularities in salary payments. Such errors and deviations include excess payments, invalid attendance, and paying salary checks to fictitious employees. PT. Data Energy Infomedia applies payroll procedures using the method of recording salary expenses. The application of the payroll procedure includes functions and documents related to payroll procedures. The implementation of the Field Work Practice aims to obtain an overview of the payroll procedure by using Zahir Accounting at PT. Data Energy Infomedia. Activities carried out during the Field Work Practice are interviews and observations on the part of the parties related to payroll. The benefits obtained from the Field Work Practice are knowing the payroll procedure by using Zahir Accounting used by PT. Data Energy Infomedia. Based on payroll procedures at PT. Data Energy Infomedia, has been running well and determined and approved by the Director of Administration and Finance. Then the delivery of salaries was immediately sent by the company through Bank BRI to reduce the occurrence of errors and irregularities in payroll.